1986
DOI: 10.1099/00222615-22-4-335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of measles-virus infection and interferon treatment on invasiveness of Shigella flexneri in HEp2-cell cultures

Abstract: Summary. The influence of measles-virus infection on the invasiveness of ShigellaJexneri in HEp2-cell cultures was studied. Bacterial invasiveness was significantly enhanced in cell cultures incubated with virus before bacterial inoculation. This effect was a function of time after introduction of virus to the cell cultures and of the concentration of virus. The increase in bacterial invasiveness was observed before production of infectious virus particles and before a cytopathic effect was evident. A similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…With respect to rotavirus, our results are in agreement with those of other authors who noticed a general increase of the invasive ability of several intestinal bacteria towards various cell lines infected with different viruses such as enteroviruses, measles virus, rotavirus and vesicular stomatitis virus (Bukholm and Degré 1984;Bukholm et al 1985Bukholm et al , 1986Bukholm et al , 1988Bukholm 1988;Marchetti et al 1992;Seganti et al 994).…”
Section: Discussionsupporting
confidence: 95%
“…With respect to rotavirus, our results are in agreement with those of other authors who noticed a general increase of the invasive ability of several intestinal bacteria towards various cell lines infected with different viruses such as enteroviruses, measles virus, rotavirus and vesicular stomatitis virus (Bukholm and Degré 1984;Bukholm et al 1985Bukholm et al , 1986Bukholm et al , 1988Bukholm 1988;Marchetti et al 1992;Seganti et al 994).…”
Section: Discussionsupporting
confidence: 95%
“…The strain was invasive in HEp-2 cell cultures [6,15]. The bacteria were cultivated on chocolate agar over-night and resuspended in PBS.…”
Section: Bacteriamentioning
confidence: 99%
“…Virus infection may also influence the susceptibility of the individual target cells to bacteria [4,9]. We have previously shown that infection of HEp-2 cells with each of several different viruses, including coxsackie B 1 virus, increased the adherence and invasiveness of enteroinvasive bacteria as Salmonella and Shigella [5][6][7][8][9]. This effect was partially reproduced with UV-light inactivated preparations containing very few infectious particles [5,6,9], indicating that the direct interaction between the virion and the cell membrane is of importance in this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…One of the crucial processes in cellular uptake of Shigella is an actin polymerisation leading to membrane ruffling, a cytoskeletal rearrangement that occurs during cellular internalisation of Shigella (Adam, Arpin, Prévost, Gounon, & Sansonetti, 1995). Hep-2 cells in culture have been used to study Shigella invasion along with the subsequent events that lead to an efficient bacterial colonisation of the epithelial monolayer (Bukholm, Modalsli, & Degré, 1986;Day, Scotland, & Rowe, 1981).…”
Section: Introductionmentioning
confidence: 98%